A study on the effects of earning per share and dividend per share on share price of Syarikat Takaful Malaysia Berhad and BIMB Holding Berhad / Sarina Abdol Sukor - Abdol Sukor, Sarina (2001)
The movement of share price is influenced by many factor for example internal and external factors. The objective of this study is to see how far Earning Per Share and Dividend Per Share affect the share price of BIMB Holding Berhad and Syarikat Takaful Sdn. Bhd. The dependent variable is share price while the independent variables are Dividend Per Share and Earning Per Share. Ail dependent variables data are taken based on the closing price from the Bloomberg while the independent variables are taken from the annual report. Linear regression method is used to see the significance of each independent variables in determining the share price and multiple liner regression method is used to see the significance of all independent variables in determining share price.